Fetal and maternal complications in macrosomic pregnancies - Cheng YK; Lao TT (Dove Medical Press, 2014)
Yvonne Kwun-Yue Cheng, Terence T LaoDepartment of Obstetrics and Gynaecology, The Chinese University of Hong Kong, Prince of Wales Hospital, Hong KongAbstract: The prediction and management of fetal macrosomia remains an obstetric challenge. Significant maternal and neonatal complications can result from the birth of a macrosomic infant, and include prolonged labor, operative delivery, postpartum hemorrhage, perineal trauma, shoulder dystocia, birth trauma, chorioamnionitis, meconium aspiration, perinatal asphyxia, low Apgar scores, neonatal hypoglycemia, and perinatal mortality. This review article discusses these maternal and perinatal risks and the management of suspected macrosomia.Keywords: macrosomia, large for gestational age, shoulder dystocia, birth trauma, perineal tear